Neonatal supplementation of oleamide during suckling ameliorates maternal postpartum sleep interruption-induced neural impairment and endocannabinoid dysfunction in early adolescent offspring rats - Qian, Linxi; Zheng, Tao; Zhao, Bowen; Wang, Weiye; Wu, Yifan (Frontiers in Nutrition, 2025)
IntroductionPostpartum sleep disturbances in women are common and can significantly affect maternal mental health and breastfeeding. However, the impact of sleep disruptions in lactating mothers on the neurological and cognitive development of their offspring has not been explored.Materials and methodsFemale Sprague–Dawley rats were subjected to chronic maternal sleep interruptions (MSI) during lactation. The offspring were divided into four groups: control, MSI, and MSI with low-dose (5 mg/kg·day) or high-dose (25 mg/kg·day) oleamide (ODA) supplementation. Behavioral performance was assessed using the Morris Water Maze (MWM). Neurogenesis and neuroinflammatory markers in the hippocampus were analyzed through immunohistochemistry, Western blotting, and Q-PCR. Levels of endocannabinoids (eCBs) were measured in maternal milk and offspring brain tissues, along with the expression of eCBs-regulating enzymes in offspring brain tissues. NE-4C cells were used to examine the effects of milk from sleep-disrupted dams on neural function.ResultsOffspring exposed to MSI showed increased escape latency, travel distance, and poor performance in the MWM probe test, indicating impaired spatial learning and memory. MSI also decreased neurogenesis markers and increased neuroinflammatory markers in the hippocampus. High-dose ODA supplementation restored behavioral performance, reduced neuroinflammation, and normalized eCBs levels and enzyme expression in the offspring’s hippocampus. Additionally, MSI altered eCBs composition in maternal milk, particularly lowering ODA and 2-AG levels. In vitro, milk from MSI dams inhibited BDNF secretion and reduced anti-inflammatory cytokine expression in NE-4C cells.ConclusionMSI during lactation disrupts eCBs signaling and induces neuroinflammation in the offspring, impairing neurodevelopment. Neonatal ODA supplementation may offer a promising intervention to mitigate the cognitive deficits and brain changes induced by MSI during lactation.